Real-world clinical validation of the Qatar pre-diabetes risk score: a cross-sectional study - Mohamed Ahmed Syed; Narjiss Sallahi; Abduljaleel Abdullatif Zainel; Halima None Bensmail; Abdelilah Arredouani (BMJ Public Health)
Introduction Pre-diabetes stands as a prominent, independent risk factor for the onset of type 2 diabetes (T2D), with 5%–10% of individuals with pre-diabetes progressing to T2D annually. The effectiveness of rigorous lifestyle interventions in averting the transition from pre-diabetes to T2D has been substantiated across multiple investigations and populations. Consequently, the clinical imperative of early pre-diabetes detection becomes unequivocal. This study assessed the validity of the recently developed pre-diabetes risk score in Qatar (PRISQ) in a real-world clinical setting.Research design and methods We recruited 1021 walk-in participants from 3 different health centres of Qatar’s Primary Health Care Corporation. Only adult people without known pre-diabetes or diabetes were included in the study. Along with blood collected for the haemoglobin A1c (HbA1c) test to confirm pre-diabetes, we recorded the age, gender, weight, waist circumference, systolic and diastolic blood pressure, nationality, smoking state and family history of diabetes. Negative predictive value, positive predictive value, sensitivity and specificity of PRISQ were computed.Results Of the 1021 participants, 797 agreed to provide blood. HbA1c test revealed that 21.9% of the 797 subjects had pre-diabetes (HbA1c between 5.7% and 6.5%) while 3.3% had undiagnosed diabetes (HbA1c≥ 6.5%). Using a PRISQ cut-off of 16, PRISQ sensitivity exceeded 90% in all subgroups of individuals aged 40 years and above, regardless of ethnicity. We did not see any significant improvement in PRISQ sensitivity when we considered the family history of diabetes.Conclusions We confirmed a good PRISQ diagnostic rate for pre-diabetes from a representative sample of the Qatar population recruited in a real-world clinical setting. PRISQ can potentially play a significant role in curbing the T2D epidemic sweeping Qatar and beyond.